Advancing Cancer Therapy with Present and Emerging Immuno-Oncology Approaches - Kamta, Jeff; Chaar, Maher; Ande, Anusha; Altomare, Deborah A.; Ait-Oudhia, Sihem (Frontiers in Oncology, 2017)
Immuno-oncology (I-O) is a young and growing field on the frontier of cancer therapy. Contrary to cancer therapies that directly target malignant cells, I-O therapies stimulate the body’s immune system to target and attack the tumor, which is otherwise invisible to, or inhibiting the immune response. To this end, several methods have been developed: First, passive therapies that enable T-Cells to fight the tumor without direct manipulation, typically through binding and modifying the intracellular signaling of surface receptors. Checkpoint inhibitors, perhaps the most well-known of I-O therapies; are an example of such. These are monoclonal antibodies that block binding of the tumor cell at receptors that inactivate the T-Cell. A variety of small molecules can achieve the same effect by affecting metabolic or signaling pathways to boost the immune response or prevent its attenuation. Drugs originally formulated for unrelated disease states are now being used to treat cancer under the I-O approach. Second, active therapies which often involve direct manipulations that occur in vitro and once introduced to the patient will directly attack the tumor. Adoptive cell transfer is the oldest of these methods. It involves the removal of T-Cells from the body, which are then expanded and genetically modified for specificity towards tumor associated antigens (TAAs), and then reintroduced to the patient. A similar approach is taken with cancer vaccines, where TAAs are identified and reintroduced with adjuvants to stimulate an immune response, sometimes in the context of antigen presenting cells or viral vectors. Oncolytic viruses are genetically modified natural viruses for selectivity towards tumor cells. The resulting cytotoxicity has the potential to elicit an immune response that furthers tumor cell killing. A final active approach is bi-specific T-Cell engagers. These modified antibodies act to link a T-Cell and tumor cell through surface receptors and thereby forcibly generate immune recognition. The therapies in each of these sub-fields are all still very new and ongoing clinical trials could provide even further additions. The full therapeutic potential of the aforementioned therapies, alone or in combination, has yet to be realized, but holds great promise for the future of cancer treatment.